State of the relict species Abies sibirica Ledeb. in the natural monument «Sinegorskaya fir grove» (Koktau mountains) - Sumbembayev, A.A.; Danilova, A.N. (KU Publ., 2021)
The article presents the results of studies of Siberian fir (Abies sibirica Ledeb.) in the natural monument «Sinegorskaya fir grove». In order to study the current state and development of the relict population field expeditions were conducted. By route-reconnaissance method the main occupied areas of the population on Mountain Medvedka were observed: the eastern, northern and western slopes, as well as two peaks. The studied population is represented by all age groups. There are 3 main types of A. sibirica Ledeb. phytocenoses: birch-fir (Betula pendula Roth, A. sibirica Ledeb.), fir (A. sibirica Ledeb.) and fir-aspen (Populus tremula L., A. sibirica Ledeb.). Parameters such as the height of mature trees, annual growth, length of young needles and the amount of young undergrowth have been determined. It has been established that the regeneration of the species directly depends on the type of phytocenosis. Based on the results of observations of the state, renewal and dispersal of Siberian fir only birch-fir communities are characterized by optimal conditions. In communities with aspen the species is severely oppressed. Diseases and pests were found in clean plantations. The limiting factors for the species are xerophytization of the habitat and the lack of sufficient soil layer. As additional protection measures to increase regeneration artificial re-sowing of seeds and planting of fir seedlings were suggested. Constant monitoring of the state of the population was proposed.
«Синегорск шыршалы тоғай» табиғи ескерткішіндегі (Көк таулары) Abies sibirica Ledeb.реликті түрінің жағдайы
Состояние реликтового вида Abiessibirica Ledeb. в памятнике природы «Синегорская пихтовая роща» (горы Коктау)
Keywords: Abies sibirica Ledeb; Kalba ridge; Sinegorskaya fir grove; relict species; cenopopulation